FREQUENCY OF DIABETES MELLITUS IN PATIENTS WITH CORONARY ARTERY DISEASE AND ITS ASSOCIATION WITH SITE OF ATHEROSCLEROTIC LESIONS - NIAZI, GZK; ADNAN, F; BUKHARI, SN; AHMED, A (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the frequency of diabetes mellitus in coronary artery disease patients and its association with the site of the atherosclerotic lesion. A comparative cross-sectional study was conducted in the Department of cardiology, CPE Institute of Cardiology, Multan, from 20 August 2019 to 19 February 2020. A totalof 234 CAD patients referred for coronary angiography were selected for the study by non-probability consecutive sampling. All patients underwent coronary angiography. Diagnosis of proximal and distal atherosclerotic lesions and diabetes mellitus. All the data were analyzed by SPSS version 23. Diabetes was found in 77 (49%) patients with proximal lesions and 19 (20.90%) patients with mid to distal lesions. This difference was statistically significant with a p-value of <0.001. Of having age 53-70 years, 74 were found in proximal lesions, and 49 patients had mid to distal site lesions with a statistically insignificant p-value of 0.308. In females, 62 patients had proximal lesions, and 16 had mid to distal lesions. This difference was statistically significant with a p-value of <0.001. Stratification was also performed based on BMI, duration of CAD, hypertension, smoking, and family history of CAD. No significant association was found between these variables and the site of the lesion. Diabetes mellitus is significantly associated with the higher frequency of proximal lesions in coronary artery disease cases.